2020
DOI: 10.1016/j.jmii.2018.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Changes in epidemiology and antimicrobial susceptibility of nontyphoid Salmonella in children in southern Taiwan, 1997–2016

Abstract: This study revealed a significant rise in serogroup D with a concomitant decline in serogroup B NTS infection in Taiwanese children. Moreover, antimicrobial resistance to third-generation cephalosporins increased in serogroup B. Continuous surveillance of NTS serogroup distribution and antimicrobial susceptibility is mandatory to formulate therapeutic strategies for NTS infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 35 publications
3
26
1
Order By: Relevance
“…More than half the NTS isolates were classified as MDR, with particularly high resistance in groups B, D, and E. These three groups also had the highest resistance rate to third-generation cephalosporin. In Taiwan, self-transferable bla CMY−2 -harboring IncI1 plasmids have been identified in several Salmonella serotypes belonging to Salmonella groups B and D (Lo et al, 2020). Since 2015, northern Taiwan has experienced an increase in Salmonella infections caused by previously rare Salmonella Anatum, a serogroup E serotype.…”
Section: Discussionmentioning
confidence: 99%
“…More than half the NTS isolates were classified as MDR, with particularly high resistance in groups B, D, and E. These three groups also had the highest resistance rate to third-generation cephalosporin. In Taiwan, self-transferable bla CMY−2 -harboring IncI1 plasmids have been identified in several Salmonella serotypes belonging to Salmonella groups B and D (Lo et al, 2020). Since 2015, northern Taiwan has experienced an increase in Salmonella infections caused by previously rare Salmonella Anatum, a serogroup E serotype.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 On the other hand, the extensive use of antimicrobials in human and food animals has led to the increasing antimicrobial resistance of Salmonella in Southeast Asian countries, including Taiwan. 4,5 Antimicrobial resistance may contribute to treatment failure, and poor clinical outcomes. 6 Salmonella serotypes are the most common pathogens for pediatric bacterial gastroenteritis in Taiwan.…”
Section: Introductionmentioning
confidence: 99%
“…6 Salmonella serotypes are the most common pathogens for pediatric bacterial gastroenteritis in Taiwan. 5 Due to the high rate of resistance to conventional antimicrobials, ciprofloxacin or ceftriaxone has become the drug of choice for the treatment of invasive salmonellosis. 7 Children with ceftriaxone-or ciprofloxacin-resistant NTS infection were previously reported in Taiwan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our disc diffusion results indicated that Ceftriaxone is an effective antibiotic against the isolate sample, and it is widely suggested for the treatment of Salmonella infections [ 46 ]. However, we found one stool and one blood isolate resistant to Ceftriaxone from the MIC result, as increasing cases have also been noticed [ 47 , 48 , 49 ]. The clinical implications of this result need further study.…”
Section: Discussionmentioning
confidence: 87%